EFFECT OF DIETARY PROTEIN AND CARBOHYDRATE LEVELS ON WEIGHT GAIN AND GONAD PRODUCTION IN THE SEA URCHIN LYTECHINUS VARIEGATUS - Heflin, Laura E. (2012)
Adult Lytechinus variegatus were fed eight formulated diets with different protein (ranging from 12 to 36%) and carbohydrate (ranging from 21 to 39 %) levels. Each sea urchin (n = 8 per treatment) was fed a daily sub-satiation ration of 1.5% of average body weight for 9 weeks. Akaike information criterion analysis was used to compare six different hypothesized dietary composition models across eight growth measurements. Dietary protein level and protein: energy ratio were the best models for prediction of total weight gain. Diets with the highest (> 68.6 mg P kcal(−-1)) protein: energy ratios produced the most wet weight gain after 9 weeks. Dietary carbohydrate level was a poor predictor for most growth parameters examined in this study. However, the model containing a protein × carbohydrate interaction effect was the best model for protein efficiency ratio (PER). PER decreased with increasing dietary protein level, more so at higher carbohydrate levels. Food conversion ratio (FCR) was best modeled by total dietary energy levels: Higher energy diets produced lower FCRs. Dietary protein level was the best model of gonad wet weight gain. These data suggest that variations in dietary nutrients and energy differentially affect organismal growth and growth of body components.